Pelaksanaan Manajemen Rekrutmen Tenaga Pendidik dalam Meningkatkan Mutu Pendidikan di MTsN 1 Sijunjung - Jamilus, Jamilus; Turrohma, Mitra (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to determine the implementation of educator recruitment management in improving the quality of education in Madrasah Tsanawiyah Negeri 1 Sijunjung. This research uses a qualitative approach with a descriptive method. The techniques used in data collection are interviews, observations, and documentation studies. Qualitative data analysis is carried out with stages of data reduction, data presentation, and conclusions. Based on the results of this study, the data found can be concluded that the implementation of educator recruitment management in improving the quality of education in Madrasah Tsanawiyah Negeri 1 Sijunjung is carried out in a simple and familial way. The stage carried out is a needs analysis, by analyzing the environmental conditions of the madrasah in the form of existing vacancies. Position analysis, by determining the general requirements for prospective educators to fill the vacancies needed, such as S1 educational qualifications. Determine the right candidate, through external sources (from outside) the madrasah environment. Choose the most appropriate method, through recommendations from educators or madrasah staff and advertisements on social media. Summoning candidates who are considered to meet the requirements of the position Selecting prospective new educators through administrative examinations. The placement of new educators was carried out directly to fill the positions needed at that time in accordance with the decision of the head of the madrasah.